Status Gizi Penerima PMT Pemulihan dengan Penerima PMT Penyuluhan pada Penderita Gizi Buruk di Kabupaten Jepara - Sarimah, Sarimah; Hutagalung, Sihol (Jurnal Riset Gizi, 2013)
Background : Malnutrition in early life may cause low quality of live; thus supplementary feeding or educational feeding programs are needed.Objective :The objective of this studyÂ  was to analyze the nutritional status difference among malnourished children after receiving suplementary feedingÂ  and educational feeding program.Method : The SubjectÂ  of the study were of 90 children under five consisting of 45 samples from subÂ  distric Kembang and 45 samples from sub distric Bangsri. Using Repeated Measure Anova SPSS program, test was used to know the difference nutritional status of the sample after one month, two months, three months giving of suplementary feeding both for the samples group of recovery suplementary feedingÂ  and education suplementary feeding receiver, and Independence Test of T â test to know the difference nutritional status between the samples group of recovery suplementary feeding and educaton suplementary feeding receiver after 1 month, 2 months, and after 3 months.Results : There was a difference nutritional status withinÂ Â  recovery suplementary feeding groupÂ  before and after receiving suplementary feeding p= 0.000. In recovery suplementary feeding group there was no significanly difference, p= 0.103. There wasÂ  no significant difference of nutritional status between group of recovery suplementary feeding receiver andeducationÂ  suplementary feeding receiver after one month by p=0.706. and also after 2 months by p value = 0.063, but after 3 months there was significant difference by p value = 0.019. .Conclution : Nutritional status moalnourished children between the group of recovery suplementary feeding and educational suplementary feeding receiver wasÂ  significantly different after 3 months.